Modulation of cytochrome P450s by strobilanthes crispus anticancer sub-fraction and its potential interaction with tamoxifen metabolism - Fen, Yong Ya (2020)
The anticancer property of Strobilanthes crispus (S. crispus) suggests its potential benefit as an adjuvant in breast cancer treatment. Potential herb-drug interaction (HDI) has always been a safety concern in pharmacotherapy as alteration in cytochrome P450 (CYP) mediated metabolism may lead to treatment failure and toxicity. In this study, the in vitro modulatory effect of a standardized sub-fraction of S. crispus (F3) on five human CYPs (CYP2B6, CYP2C9, CYP2C19, CYP2D6 and CYP3A4) was first investigated. Negligible inhibitory effects of F3 on all the five CYPs were observed, with IC50 values more than 100-fold higher in comparison to known CYP inhibitors. The use of F3 in conjunction with conventional breast cancer therapy using tamoxifen (TAM) could be a strategy to maximize the therapeutic efficacy. Thus, the investigation of the interaction between F3 and TAM is crucial. The potential HDI was first investigated through evaluating the influence of F3 on CYP mediated TAM metabolism in vitro. F3 demonstrated weak mixed-type inhibition towards CYP2D6 catalyzed TAM 4-hydroxylation and CYP3A4 catalyzed TAM N-desmethylation. The combined effect of TAM and F3 on the viability of MCF- 7 cell line was then investigated. A buffering antagonistic effect was observed from the combined treatment. The outcome of this study suggests the low possible interactions between F3 and TAM as well as the five CYPs catalyzed drug metabolism. Nevertheless, further studies are warranted to evaluate the efficiency and safety of the drug combination treatment in vivo.